Syndrome-Analysis of New Media and Political Economy in 21st Century - Ong’ong’a, Oloo Daniel (Journal of New Media and Mass Communication, 2020)
In recent years, social media digital platforms are concentrated in the hands of the few individuals and corporate bodies globally. These giants include Facebook, WeChat, Amazon, Apple, and Google, who operate in the franchised model for-profit, political and economic signification. Their abilities to manipulate data, censor it, and repackages it gives them an upper hand in setting economic and political agenda in these new media markets. With the financial muscles at their disposal, these corporations have continued to mine individual data for their benefits, which is not limited to advertising but also influencing individuals’ behaviours in political and social-economic development issues. Datafication and ’’platformization’’ of individual’s data have paved the way for which there is a need to understand the new political economy of subjectivism. Personal information is used for the commodification of messages to make them appealing and create economic imbalances. Although individuals using such kind of platforms benefit from various advantages, which include social development and economic mileages that it is associated with them, they found it a challenge when it comes to the issue of privacy, unwarranted marketing messages, and intrusion into their solicitudes. Personal data is used for profit, tools for research development of new ideologies to direct and make vital political and economic decisions. This article explores the various ways in which the new media political, economic giants have strategized in the influencing of privatization of information for maximization of profits as well as creating barriers to access of vital information by their consumers.